2011
DOI: 10.4049/jimmunol.1101050
|View full text |Cite
|
Sign up to set email alerts
|

Control of Pathogenic CD4 T Cells and Lethal Immunopathology by Signaling Immunoadaptor DAP12 during Influenza Infection

Abstract: Immunopathology is a major cause of influenza-associated morbidity and mortality worldwide. However, the role and regulatory mechanisms of CD4 T cells in severe lung immunopathology following acute influenza infection are poorly understood. In this paper, we report that the emergence of immunopathogenic CD4 T cells is under the control of a transmembrane immunoadaptor DAP12 pathway during influenza infection. We find that the mice lacking DAP12 have unaltered viral clearance but easily succumb to influenza inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…The present study expands current knowledge of the involvement of DAP12 in host defense against intracellular microorganisms (12,15,38) and influenza virus (33,38), showing for the first time that DAP12 impairs host defense during respiratory tract infection caused by S. pneumoniae. Our studies were limited to one pneumococcal strain.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present study expands current knowledge of the involvement of DAP12 in host defense against intracellular microorganisms (12,15,38) and influenza virus (33,38), showing for the first time that DAP12 impairs host defense during respiratory tract infection caused by S. pneumoniae. Our studies were limited to one pneumococcal strain.…”
Section: Discussionsupporting
confidence: 70%
“…In a colitis model induced by streptomycin administration and oral infection with Salmonella Typhimurium, dap12 -/mice had higher bacterial burdens in their ceca than Wt mice, which was associated with increased local inflammation (15). In this respect, it should be noted that the lung is of particular interest for studies on DAP12 and antibacterial defense, considering its constitutive expression in this organ (32,33). Although this study (15) hinted at a role for DAP12 in antibacterial defense, at least in the intestine, dap12 -/mice displayed reduced bacterial loads after IV infection with the intracellular bacterium L. monocytogenes (12).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have discovered that DAP12 signaling following C. neoformans challenge contributes to an immune response that is detrimental to the host. Although other studies have demonstrated that DAP12 can be either beneficial or detrimental depending on the microbial and tissue context (22)(23)(24)(25)(26)(27)(28), this study represents the first evidence that DAP12 signaling can be unfavorable to the host during a fungal infection. The downstream effects of this DAP12-mediated pathway appear to be 3-fold: increased pulmonary eosinophilia and suppression of the antifungal activity of both NK cells and macrophages.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, DC-ITAM modulation of TLR, GM-CSF or IFNAR signaling pathways might selectively alter external signals regulating inflammatory effector responses [9]. For example, Dap12 deficiency in mice results in altered activity of antigen-specific T cells [10][12]. Moreover, Dap12 and FcRγ deficiency results in complete protection against induction of experimental autoimmune encephalomyelitis (EAE) [8].…”
Section: Introductionmentioning
confidence: 99%